Ambiguities in the Search for Christian Unity: The General Council of Protestant Evangelical Missions in Korea, 1905–1912 - Seo, Dongjun (The journal of ecclesiastical history, 2022)
The formation of the General Council of Protestant Evangelical Missions in Korea in 1905 with the ultimate objective of achieving church union beyond denominational boundaries is a significant but neglected episode in the twentieth-century ecumenical movement. The council was reorganised in 1912 as the Federal Council of Protestant Evangelical Missions in Korea, which marked a significant shift of ecumenical objectives from institutional union to missionary cooperation. This article examines why and how this change happened and its implications for interpretations of the wider ecumenical movement in the twentieth century.